2019
DOI: 10.1177/1687814018817421
|View full text |Cite
|
Sign up to set email alerts
|

A simulation and experimental study on the operating characteristics of a solenoid gas injector

Abstract: Purpose of this study is to develop a solenoid actuator that can be used for natural gas injector. Operation of the solenoid injector is described by two mathematical models including an electrical model and a mechanical model. The solenoid injector is also modeled and simulated in Maxwell and Simplorer based on the specifications of a real solenoid injector. The operating characteristics of the solenoid injector, including the current, electromagnetic force, and displacement of the plunger, are investigated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Hung and Lim [12] presented a simulation study to improve the electromagnetic force of a solenoid injector, in which they changed the cross-sectional shape of the coil, thickness of the cut-off of the sleeve, and the relative position between the coil and plunger to obtain the highest electromagnetic force. The improvements of electromagnetic force based on the effects of structural parameters were also found in other studies [13][14][15][16][17][18][19][20][21][22]. The previous studies [2,[9][10][11][12][13][14][15][16][17][18][19][20][21][22] provided useful information when improving electromagnetic force in a solenoid by optimizing design parameters such as plunger shape, plunger mass, coil shape, coil turns, coil location, air gap, pole radius, and yoke thickness of the magnet.…”
Section: Introductionsupporting
confidence: 58%
“…Hung and Lim [12] presented a simulation study to improve the electromagnetic force of a solenoid injector, in which they changed the cross-sectional shape of the coil, thickness of the cut-off of the sleeve, and the relative position between the coil and plunger to obtain the highest electromagnetic force. The improvements of electromagnetic force based on the effects of structural parameters were also found in other studies [13][14][15][16][17][18][19][20][21][22]. The previous studies [2,[9][10][11][12][13][14][15][16][17][18][19][20][21][22] provided useful information when improving electromagnetic force in a solenoid by optimizing design parameters such as plunger shape, plunger mass, coil shape, coil turns, coil location, air gap, pole radius, and yoke thickness of the magnet.…”
Section: Introductionsupporting
confidence: 58%
“…A test bench for the fuel injection characteristics of electronic injector was built, in which the software and hardware implementation scheme of the test technology was studied. On this basis, the intelligent test system for the fuel injection characteristics of the electronic injector was successfully developed [ 17 , 18 ].…”
Section: Design and Analysis Of The Fuel Injection Systemmentioning
confidence: 99%
“…Their simulation results showed that when the air gap decreased, the electromagnetic force increased. Besides the studies mentioned above, there are also other studies related to improving the operating performance of solenoids under influence of working conditions and structural parameters [13][14][15][16].…”
Section: Introduction *mentioning
confidence: 99%